THE EFFECT OF SERVICE QUALITY ON CUSTOMER RETENTION THROUGH COMMITMENT AND SATISFACTION AS MEDIATION VARIABLES IN JAVA EATING HOUSES - Sari, Sulva Widya; Sunaryo, Sunaryo; Mugiono, Mugiono (Universitas Brawijaya, Indonesia, 2018)
The culinary business is faced with high competition to keep their customers, these conditions cause Javanese Restaurant expected to create customer retention through service quality. Therefore, this study aims to determine the relation of service quality, commitment, and satisfaction on customer retention and the effect of commitment and satisfaction as a mediator of service quality on customer retention. The analysis is based on 100 respondents who were customers of Javanese Restaurant in Kuta Utara Bali through a survey questionnaire. The measurement model of research hypothesis analysis using Partial Least Square (PLS) procedure. The result of the research indicates that service quality and commitment have no significant effect on customer retention while other variables have a significant effect. The effect of customer satisfaction fully mediates on the relationship of service quality on customer retention. This study contributes to a restaurant to combine strategies of improving service quality, commitment, and customer satisfaction, so that customer retention is realized through repeat purchases.